1974
DOI: 10.1111/j.1365-2389.1974.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF PHOSPHATE‐REACTIVE SITES OF HYDROUS ALUMINA FROM PROTON CONSUMPTION DURING PHOSPHATE ADSORPTION AT CONSTANT pH VALUES

Abstract: The amounts of hydroxyl ions released from hydrous alumina during phosphate adsorption were measured at constant pH values and at different phosphate concentrations using an automatic titrator. The hydroxyl ions released were plotted against phosphate adsorbed and the equations that gave best fit to the data were differentiated. The variation in the differentials (dOH/dP) with increasing phosphate adsorption was consistent with the theory, proposed below, on the type of sites responsible for phosphate adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Figure 6 shows that at pH 5.5 in the 0.1 M NaCI0 4 system the amount of OH displaced for Se(IV) adsorption on AI-l was larger than that for As (V) and that Se(IV) replaced a larger amount ofOH on Fe-I (pzc=7.5) than AI-I (pzc= 9.0). Acid consumption could arise either from OH released or H+ consumed by dissociated oxyanion ions (RAJAN et aL 1974). As these facts can not be ascribed to the acid consumption based on the difference of the first and second dissociation constants between As(V) and Se(lV), it is concluded that Se(lV) preferably replaced a larger amount of OH than As(V) and that the lower pZc of Fe-l induced the release of a large amount of OH.…”
Section: Ligand Exchange Of Oh and Oh 2 With Oxyanionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 6 shows that at pH 5.5 in the 0.1 M NaCI0 4 system the amount of OH displaced for Se(IV) adsorption on AI-l was larger than that for As (V) and that Se(IV) replaced a larger amount ofOH on Fe-I (pzc=7.5) than AI-I (pzc= 9.0). Acid consumption could arise either from OH released or H+ consumed by dissociated oxyanion ions (RAJAN et aL 1974). As these facts can not be ascribed to the acid consumption based on the difference of the first and second dissociation constants between As(V) and Se(lV), it is concluded that Se(lV) preferably replaced a larger amount of OH than As(V) and that the lower pZc of Fe-l induced the release of a large amount of OH.…”
Section: Ligand Exchange Of Oh and Oh 2 With Oxyanionsmentioning
confidence: 95%
“…Several authors have suggested the existence of the ligand exchange of oxyanions on the hydrated oxides of iron and aluminum (MULJADI et al 1966;HINGSTON et aL 1968bHINGSTON et aL , 1972RAJAN et aL 1974;PARFITT and RUSSELL 1977;RYDEN et al 1977). However, there is a lack of information on the OH and OH 2 ligand exchange for the adsorption of oxyanions such as As(V) and Se(V) at a given pH.…”
mentioning
confidence: 99%
“…1). The results of Anderson et al (1974) (Rajan et al 1974;Rajan 1975Rajan , 1976. Atthe beginning ofthe adsorption, the adsorption sites were surrounded by a higher concentration of the adsorbate; the reaction proceeded more easily.…”
Section: Quantity Of P Adsorbedmentioning
confidence: 97%
“…Upon ageing, bonding of P onto the oxide surfaces also becomes stronger (Kaila 1965) as monodentate bonds are converted to bidentate and binuclear ones (Kafkafi et al 1967). Continuous weathering of soil minerals produces new Al and Fe hydroxide faces and new sites for P sorption are generated (Rajan et al 1974). Phosphorus can even be embedded (occluded) in the oxides and lose contact with the soil solution.…”
Section: P Stock and P Supply To Plantsmentioning
confidence: 98%